(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Post-stroke depression (PSD) is one of the most common neuropsychiatric complications following cerebrovascular accidents and significantly affects functional recovery, quality of life, and mortality. The prevalence of PSD varies widely depending on diagnostic criteria and timing of assessment, ranging from 20% to 60%. This review aims to summarize current knowledge on the clinical manifestations, risk factors, pathophysiological mechanisms, and management strategies of post-stroke depression. Special attention is given to biological, psychological, and social determinants contributing to the development of depressive symptoms after stroke. Early recognition and appropriate treatment of PSD are essential for improving rehabilitation outcomes and reducing long-term disability. Understanding the multifactorial nature of PSD allows clinicians to implement comprehensive and individualized therapeutic approaches.